Cardiovascular magnetic resonance in the guidelines of the European Society of Cardiology: a comprehensive summary and update - Florian von Knobelsdorff-Brenkenhoff; Jeanette Schulz-Menger (Journal of Cardiovascular Magnetic Resonance, 2023)
Abstract Background Cardiovascular magnetic resonance (CMR) has been established as a valuable tool in clinical and scientific cardiology. This study summarizes the current evidence and role of CMR in the guidelines of the European Society of Cardiology (ESC) and is an update of a former guideline analysis. Methods Since the last guideline analysis performed in 2015, 28 new ESC guideline documents have been published. Twenty-seven ESC practice guidelines are currently in use. They were screened regarding CMR in the text, tables and figures. The main CMR-related sentences and recommendations were extracted. Results Nineteen of the 27 guidelines (70.4%) contain relevant text passages regarding CMR in the text and include 92 specific recommendations regarding the use of CMR. Seven guidelines (25.9%) mention CMR in the text, and 1 (3.7%, dyslipidemia) does not mention CMR. The 19 guidelines with recommendations regarding the use of CMR contain 40 class-I recommendations (43.5%), 28 class-IIa recommendations (30.4%), 19 class-IIb recommendations (20.7%) and 5 class-III recommendations (5.4%). Most of the recommendations have evidence level C (56/92; 60.9%), followed by level B (34/92; 37.0%) and level A (2/92; 2.2%). Twenty-one recommendations refer to the field of cardiomyopathies, 21 recommendations to stress perfusion imaging, 20 recommendations to vascular assessment, 12 to myocardial tissue characterization in general, 8 to left and right ventricular function assessment, 5 to the pericardium and 5 to myocarditis. Conclusions CMR is integral part of the majority of the ESC guidelines. Its representation in the guidelines has increased since the last analysis from 2015, now comprising 92 instead of formerly 63 specific recommendations. To enable patient management in accordance to the ESC guidelines, CMR must become more widely available.